Non Performing Financing Dan Financing To Deposit Ratio Dalam Mempengaruhi Profitabiltas Perbankan Syariah Di Indonesia - Udik Jatmiko (LPPM ISNJ Bengkalis, 2021)
This study aims to show the effect of non-performing financing and financing to deposit ratios on return on assets in Islamic banking listed on the Indonesian capital market for the 2016-2020 period, either partially or simultaneously. The population in this study is Islamic banking which is listed in the Indonesian capital market with a research sample of 6 Islamic banks located in the East Java region. The analysis technique uses a classical assumption test, multiple linear regression test, coefficient of determination, t-test, and F-test. The research results explain that partially non-performing financing significantly affects return on assets in Islamic banking listings in the Indonesian capital market period 2016-2020. Meanwhile, the financing to deposit ratio does not affect the return on assets of Islamic banking listed on the Indonesian capital market for the 2016-2020 period. This research can be a reference for Islamic banks listed on the Indonesian capital market in managing their financing more optimally so that non-performing financing does not occur, leading to decreased profitability.